Fecal sludge-derived pellet fertilizer in maize cultivation - Pradhan, Surendra K.; Nikiema, Josiane; Cofie, Olufunke O.; Heinonen-Tanski, H.; Drechsel, Pay (IWA Publishing, 2016)
Fecal sludge (FS) contains significant amounts of plant nutrients and organic matter although it also contains pathogens. Therefore, FS can be used as fertilizer after proper sanitization. This study was designed to test dried fecal sludge (DFS)-based pellet fertilizers on maize cultivation. The DFS fertilizers were produced by composting, co-composting with sawdust, or irradiated by gamma-irradiation, and then nitrogen-enriched and pelletized using gelatinized or gamma-irradiated cassava starch. These DFS pellet fertilizers were compared to each other and to no-fertilization, mineral fertilizer, and agro-industrial waste compost. The fertilizer applications were 150 or 210 kgN/ha. Maize was cultivated in pots containing Cambisol and Ferric Lixisol growth media. The EC-SDFS-PG pellet (DFS + sawdust co-composted, enriched with nitrogen and pelletized) at a rate of 210 kgN/ha produced the highest maize yield (4.4 ton/ha) among all other treatments, while mineral fertilizer produced 3.9 ton/ha. It is concluded that the EC-SDFS-PG pellet produces similar or higher maize yields than mineral fertilizer and more than the agro-industrial compost in both growth media types.